Quantitative Analysis and Comparison of Symmetric Cryptographic Security Algorithms - Mahaba Saad; Khalid Youssef; Hala Abdel-Kader (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Nowadays, the rapid evolution of communication systems offers, to a very large percentage of population, access to a huge amount of information and a variety of means to use in order to exchange personal data. Hence the search for the best solution to offer the necessary protection against the data intruders’ attacks along with providing these services in time is one of the most interesting subjects in the security related communities. Cryptography is usually referred to as “the study of secret”. Encryption is the process of converting normal text to unreadable form. There are a variety of encryption algorithms have been developed. This paper provides quantitative analysis and comparison of some symmetric key cryptographic ciphers (DES, 3DES, AES, Blowfish, RC5, and RC6).  The quantitative analysis approach is a step towards optimizing the security operations for an efficient next generation family of network processors with enhanced speed and power performance. A framework will be proposed as a reference model for quantitative analysis of security algorithm mathematical and logical operations.